Meeting in the Middle: Strategies for Successful Union-Administration Collaboration - Kristi Haik; Mary Elizabeth Zimmer (Academic Chairpersons Conference Proceedings, 2019)
Presenters and participants will discuss best practices and develop strategies to create a collaborative working environment within a higher education-union culture.
Keywords: Union; collective bargaining; faculty; staff; clerical; university culture; relationship building